A Realistic Approach to Maternal-Fetal Conflict - Hornstra, Deborah (The Hastings Center report, 1998)
We should not think of babies as having a right to be born healthy. We cannot say what such a right involves, and if we could, enforcing it would infringe on the mother's most basic rights. Most importantly, positing such a right casts the fetus and mother as adversaries, and so destroys the maternal-fetal relationship.